Instruments of the divinity providence and praxis in the Foundation of the Society of Jesus - Ginhoven Rey, Christopher van, 1979- (Leiden ; Boston : Brill, 2013)
Focusing on Saint Ignatius of Loyola's conception of Jesuits as the instruments of a laboring God, Instruments of the Divinity explores the philosophical and theological roots of the metaphor of the instrument and its place in the social imaginary of the Jesuit order.
Print version record.
Includes bibliographies and index.
Keywords: Jesuits; Ignatius, -- of Loyola, Saint, -- 1491-1556.; Jesuits; Exercitia spiritualia (Ignatius, of Loyola, Saint); Ignatius, -- of Loyola, Saint, -- 1491-1556.; Jesuits; Providence and government of God -- Christianity; RELIGION -- Christian Life -- General; Providence and government of God -- Christianity; Electronic books; Electronic books